ANALISIS ANALYSIS OF THE RELATIONSHIP BETWEEN NURSES' CAREER LEVELS AND WORKPLACE VIOLENCE IN HOSPITALS IN ACEH PROVINCE - Faidhil Faidhil; Ardia Putra (Getsempena Health Science Journal, 2026)
Nurses are one of the health professions that are highly vulnerable to violence in the workplace. Violence against nurses, whether physical or non-physical/psychological, can have a negative impact on the quality of work and nursing services. The purpose of this study was to determine the relationship between the career level of clinical nurses and workplace violence, including physical violence and psychological violence against nurses at the Aceh Provincial Hospital. This study is quantitative a cross-sectional study design. The research employed a total sampling approach with 127 respondents meeting the inclusion criteria. Data on violence were collected using the Workplace Violence in the Health Sector (WPVHS) questionnaire, while career-level variables were collected from demographic data. Data analysis was performed using descriptive statistics and the chi-square test. The results showed that the career level variable was not related to physical violence, but it was related to psychological/non-physical violence, with a p-value of 0.000. Based on the research results, it was proven that nurses are highly susceptible to violence in the workplace. Low career level is a predictor of violence. Violence can reduce nurse performance, increase turnover, anxiety, work stress, depression, sleep disorders, high fatigue levels, post-traumatic stress disorder (PTSD), physical injury, and death